Oral Hygiene Practice among 18-year-old Norwegian Adolescents Using Health Belief Model: A Cross-Sectional Study - Nasir, Elwalid Fadul; Vu, Johnny (European Journal of Dentistry, 2021)
Objectives The aim was to compare oral hygiene practice (brushing/flossing) among 18 years old from two regions, Hordaland County, Norway, and possible perceptional correlates using the Health Belief Model.Materials and Methods The participants from six municipalities from the south district with high prevalence of dental caries to six municipalities from the rest of Hordaland county, with low prevalence of dental caries (control), using a web-based questionnaire. Statistical analyses: the Mann–Whitney U test was used and the t-test for independent samples. Bivariate and logistic regression analyses to examine associations.Results A total of 416 people participated. The south district’s participants had lesser percentage brushing twice a day and flossing at least once a day, they significantly visited lesser the dental service, perceived more susceptibility to dental caries, and lower benefits of brushing/flossing compared with the controls. Girls (odds ratio [OR]: 0.34) who perceived higher severity of dental caries (OR: 1.86), higher self-identity (OR: 2.14), and lesser barriers to brushing (OR: 0.14) had higher odds to brushing twice a day compared with their counterparts. Girls (OR: 0.34) who perceived higher severity of dental caries (OR: 2.34), higher benefits (OR = 2.8), and lesser barriers to flossing (OR = 0.23) had higher odds to flossing at least once a day compared with their counterparts.Conclusion South district’s participants significantly had some of risk factors to the recommended brushing/flossing practice compared with the control and these might help in explaining the difference in oral hygiene practice.
Keywords: oral hygiene practice; brushing; flossing; health belief model; 18 years old; adolescence; Norway